Synthesis and Evaluations of Novel Apocynin Derivatives as Anti-Glioma Agents - Tao Yang; Tao Yang; Tao Yang; Da-Wei Zang; Da-Wei Zang; Wei Shan; Wei Shan; Wei Shan; An-Chen Guo; An-Chen Guo; An-Chen Guo; Jian-Ping Wu; et al. (Frontiers Media S.A., 2019)
Apocynin (4-hydroxy-3-methoxyacetophenone) is a natural polyphenolic compound with multiple biological activities. In the present study, a series of apocynin derivatives were designed and synthesized. The in silico ADMET prediction, blood-brain barrier (BBB) penetration assay, anti-NADPH oxidase activity, reactive oxygen species (ROS) levels, and anti-glioma effects of these apocynin derivatives were evaluated. The anti-glioma mechanisms of candidate compounds were studied by ﬂow cytometer and Western blot. The results showed that D31 exhibited higher BBB penetration, increased ROS generations and significant anti-glioma effects both in vitro and in vivo. Further studies showed that D31 inhibited the activations of NF-κB pathway. Overall, our data demonstrated that D31 inhibited growth and induced apoptosis of glioma, which might be caused by ROS-related NF-κB activation. The current study suggested that D31 could be further explored for its potential use in anti-glioma therapy.